Carbohydrate feedings improve 1 h time trial cycling performance - Jeukendrup, A.; Brouns, F.; Wagenmakers, A. J. M.; Saris, W. H. M. (International Journal of Sports Medicine, 1997)
Carbohydrate (CHO) feedings have been shown to improve endurance performance at moderate intensities (60-70% VO2max) and of more than two hours duration. This study found that ingesting CHO at a rate of 1 gm/min during exercise, improved performance in a cycling task of approximately one hour duration. Implication. CHO feeding during exercise improves performance when the task duration is of one hour or longer.